Agroecologia e educação do campo: meios de promover a permanência do jovem no campo? - Kusniewski, Fernanda Paula Piran (2018)
Youth retention in rural communities is a determining factor for family succession in farms countrywide. However, some elements are involved to this end, mainly improved education and employment. In this sense, this study aimed to assess the prospects of young peasants and their relationship with Agroecological Production and Rural Education, in the settlements Ireno Alves dos Santos and Marcos Freire, in Rio Bonito do Iguaçu, Paraná State (Brazil). We investigated two farmer groups, one composed of 16 families involved in agroecological or transitional farming system, and the other including 16 families in a conventional production system. The survey was performed with 17 youngsters from the first group and 18 from the second; they all aged between 13 and 29 years. Further, 23 youngsters enrolled in the last year of high school of a schoolhouse at the settlement of Ireno Alves dos Santos were also surveyed. The study was intended to verify the relevance of an Agroecological Production and Rural Education as enablers of youth retention in farm communities. In terms of methodology, it was a qualitative, exploratory, and descriptive approach, where data collection was made through field research along with semi-structured interviews and surveys. The families were questioned about the production process used in the referred property, its shortcomings, strengths, and about the paternal influence on youngsters’ decisions, among other aspects. Open-ended and close-ended questionnaires were administered both to young people entered into the productive system and the school attendees. The goal was to picture the reality experienced by these young people in and outside the family unit, as well as their portrayals about rural and urban lifestyles. One of the greatest focus was to know what their perspectives on remaining in the rural units are. Agroecological farming systems have been facing several challenges in terms of certification, marketing, technical support, public capital programs and, above all, an improved environmental awareness of farmers. Likewise, Rural Education has faced other issues, mainly because of the distancing between current legislation and school daily activities. By surveying the schoolgoers, we realized that the principles of Rural Education are only procedural, through normative ruling and related legislation, but were not concretely applied in the school routine. Thus, both Agroecological Production and Rural Education are not yet strong elements to be used in the fight against the lack of opportunities and affirmation of young settlers living in the studied location. Moreover, no significant relationship was found between the youth retention prospects and the used farming systems or rural education model. Even because the factors Agroecological Production and Rural Education have been through many challenges, which have to be faced until they become more consistent from theoretical and practical points of view. Furthermore, the main reasons for rural outflow of youngsters lie in the search for improved schooling and employment.